Ensino, pesquisa e extensão em tempos de pandemia: uma análise da preceptoria em saúde no Hospital Universitário Lauro Wanderley - Frazão, Cristiane da Silva Costa (2021)
This study aims to analyze the actions adopted for innovation in teaching, research and extension at HULW in the context of the pandemic of COVID-19, seeking to characterize the strategies used for the preceptorship of students after the pandemic context and build an approach to evaluate the effectiveness of these strategies with a focus on performance in health preceptorship.As for the methodological path, a research is classified as descriptive, with a qualitative approach, configuring itself as a case study. The research subjects were HULW's preceptors and medical and nursing residents who maintained their activities during the pandemic period. In relation to data collection, it was carried out through interviews with the preceptors and the application of questionnaires with the residents. Based on the results, it was possible to conclude that innovations were necessary to maintain teaching, research and extension activities within the scope of preceptorship during the pandemic. Among them, the suspension of presencial theoretical activities, which began to occur remotely, the maintenance of practical activities only for residents who already worked in specialties compatible with the nature of the care provided to patients positive for COVID-19, as well as the training of these so that they could exercise their activities with attention to the established biosafety rules. It could be inferred that the performance in this pandemic moment was a differential for the training of the residents who participated in this research, not only practical learning, but also in the other factors related to the integral training of these health professionals. As a contribution to the studied scenario, a digital tutorial with preventive measures was proposed to be implemented in the preceptories of students to face the pandemic of COVID-19.